Revitalization of Civic Disposition to Improve Digital Ethics in the Era of 5.0 Society at Dharma Patra Private High School Pangkalan Brandan T.P 2022/2023 - Orlin, Stefanie; Lahmuddin, Lahmuddin (Holistic Science, 2023)
This research aims to find out how the digital ethics of grade XI students at SMA Swasta Dharma Patra Pangkalan Brandan and how to revitalise civic disposition to improve digital ethics in the era of 5.0 society for grade XI students at SMA Swasta Dharma Patra Pangkalan Brandan. This type of research is descriptive analysis with a qualitative approach that aims to describe or describe a problem, situation or phenomenon accurately and systematically. The techniques used in this research are observation, interview and documentation while the data analysis technique by reducing data, presenting data and verifying or drawing conclusions so as to provide an overview of the problem being studied. The results of this study indicate that revitalising civic disposition to improve digital ethics in the era of 5.0 society at Dharma Patra Pangkalan Brandan Private High School can be done through PPKN learning. Because the function of civic education is as a means to form smart, skilled and personality citizens who are loyal to the nation and state of Indonesia by reflecting themselves in habits of thought and action as mandated by Pancasila and the 1945 Constitution